A Mural Erased: Urban Art, Local Politics and the Contestation of Public Space in Mashhad. (November 2016) - Zarkar, Rustin
Over the decade following the 1979 Revolution, Iran's urban landscape was dramatically refashioned by municipality-led beautification programmes aimed at rejuvenating cityscapes through new public art installations. The newly established government sought to erase or subvert the symbols and public displays of the old regime and replace them with a new visual vocabulary situated within the grand narrative of the Islamic Republic. City streets, boulevards, squares and building façades became sites for a new imagery that championed a revolutionary form of Islam and advocated anti-imperialist and anti-American sentiments, replacing wartime murals with more hopeful visual motifs. This photo-essay captures the public art installations in the city of Mashhad, revealing how the municipality's beautification programme is directly affected by local politics, in an attempt to offer a fuller picture of modern life and politics in Iran.